Pengaruh Lokasi, Personal Selling, dan Sales Promotion terhadap Minat Masyarakat Menjadi Nasabah di BPRS Bangun Drajat Warga - Arfiani; Khoiruddin, Akhmad Yusuf (Journal of Business Management and Islamic Banking, 2022)
Research Aims: Sharia People's Financing Bank (BPRS) is a financial institution that conducts its activities based on sharia principles. Currently, BPRS is growing in Indonesia, with the development of BPRS, many new BPRS will appear and of course will lead to competition between BPRS and others. Location as a company's operational place has a strategic function because it can determine the achievement of a company, while personal selling is an important partner in world marketing communications. The sales promotion as a form to present the product. Design/methodology/approach: In this study using quantitative methods that aim to determine the effect of location, personal selling, and sales promotion on public interest in becoming customers at BPRS Bangun Drajat Warga. For the purpose of this study, 110 samples were used from the community around the BPRS Bangun Drajat Warga head office, domiciled in a radius of 2 km from the BPRS Bangun Drajat Warga head office, using a purposive sampling technique.Put your text here (Cambria 10pt). Research Findings: Based on the results of the research that the location t test has no effect and is not significant because the t count < t table is -0.532 < 1.982. In personal selling based on the t test that personal selling has a positive and significant effect because the t count > t table is 2,000 > 1,982 and sales promotion based on the t test has a positive and significant effect because the t count > t table is 3,361 > 1,982